Classification and Ordination of Vegetation in Shahbaz Gari, District Mardan (Global Journal of Science Frontier Research, 2015)
A survey of natural vegetation of Shahbaz Ghari, District Mardan was undertaken in 2013-2014. Total 48 plant species in 9 communities were observed by Hierarchical Cluster Analysis and Detrended Correspondence. Plant species of each community are presented together which showed the correlation between species. The results represent that group A1a have 6 species, group A1b (2 species), A2 (3 species), group B1a (9 species) group B1bi (13 species), group B1bii (6 species), group B2 (9 species) and total important value was 53.9, 27.4, 37.6, 43, 44.9, 36.6 and 56.5 respectively. The Detrended Correspondence Analysis showed that the highest weighted mean species scores 2.88% was presented by Stellaria media followed by Boerhaavia procumbens (2.76%) and Chenopodium album (2.75%). Classification and ordination techniques provided very similar results based on the floristic composition and communities similarity. The results produced the source for the mapping division of vegetation.
Keywords: cluster analysis; species weight; community structure; vegetation